2020
DOI: 10.4103/ijmbs.ijmbs_36_20
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics and clinical manifestations of systemic sclerosis in Benghazi, Libya

Abstract: Background: Systemic sclerosis (SSc) is a rare, heterogeneous autoimmune disease characterized by skin fibrosis, vasculopathy, and internal organ involvement. This study aims to determine the frequency of clinical manifestations of SSc among Libyan patients in Benghazi. Patients and Methods: Thirty patients (28 females) attended the Rheumatology Clinic at Benghazi Medical Center between January 2016 and December 2019. They were diagnosed to have SSc according to American College of Rheumatology/European League… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Regarding the prevalence of the different subtypes, this study has shown that 54.5% of the patients presented with the diffuse subset, leaving only 45.5% in the lcSSc group. This finding emphasizes regional differences in populations, where Emirati patients seem to be similar to other Arab 18,19 and African American individuals (GRASP cohort), 26 exhibiting higher frequencies of the dcSSc than Caucasian 1,4,10 or Southeast Asian populations. 16,27 It could also be related to the fact that other studies included other SSc subsets and conditions, such as ssSSc, overlap syndromes, prescleroderma, and undifferentiated subsets.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Regarding the prevalence of the different subtypes, this study has shown that 54.5% of the patients presented with the diffuse subset, leaving only 45.5% in the lcSSc group. This finding emphasizes regional differences in populations, where Emirati patients seem to be similar to other Arab 18,19 and African American individuals (GRASP cohort), 26 exhibiting higher frequencies of the dcSSc than Caucasian 1,4,10 or Southeast Asian populations. 16,27 It could also be related to the fact that other studies included other SSc subsets and conditions, such as ssSSc, overlap syndromes, prescleroderma, and undifferentiated subsets.…”
Section: Discussionmentioning
confidence: 51%
“…1,4 Nevertheless, studies have revealed heterogeneity of the disease presentations, phenotype, and clinical variants among populations (gender, geographical, partly due to genetic and ethnic heterogeneity). 1,16,17 Reports from other Arabic countries 18,19 were mainly limited by the small sample size and heterogeneity of the included participants, which might not reflect the exact characteristics of a given population. Thus, local registries are paramount for better understanding of clinical and serological features, allowing for the implementation of patient-tailored strategies for early detection and better management and quality of care.…”
Section: Introductionmentioning
confidence: 99%